Peran Komunitas Gusdurian Dalam Menerapkansikap Religius Dan Toleransi Melalui Strategi Komunikasi Persuasif Di Universitas Nadhatul Ulama Sidoarjo - Solikha, Sofia Imro'atus; Munif, Munif; Jamhuri, M. (CV. Satria Jaya, 2023)
The purpose of the research is to find out how the role of the Gusdurian community in implementing religious attitudes and tolerance and to find out how the application of religious attitudes and tolerance through persuasive communication strategies at Unusida. This study uses a qualitative approach with a case study type. The data sources required are primary data and secondary data. Data collection techniques with observation, interviews, and documentation. And the data analysis used is data reduction and data presentation. The results showed that the role of the Gusdurian community in implementing religious attitudes was that students became active in attending prayer congregations, not a few students also wore kopyahs as a symbol to emulate the figure of Gusdur, became more active in lectures and had quality public speaking. Meanwhile, in the attitude of tolerance, students do not differentiate between the castes of other students, mingle with all groups, and are able to become mediators in the event of conflict problems around them. If the application of religious attitudes, through psychodynamic strategies, namely religious and interfaith knowledge discussion activities, sociocultural strategies through banjari activities, nadhatul syubban. Whereas in the attitude of tolerance through psychodynamic strategies, namely Gusdurian care, regular discussions discussing Gus Dur's exemplary example, sociocultural strategies, namely ngobar activities, visits to celebrations of religious holidays, and construction strategies, namely socialization of social media.